Private production of a public good in the information age - Zweifel, Peter; XU, Xian (Archives of Business Research, 2020)
The objective of this contribution is to model the behaviour of IT specialists who engage in open source activity while on the job thus privately provide a public good. Both the regular and the social types are assumed to be interested in income and leisure; however, for the social types effective leisure is enhanced by the number of external users, which enhances their intrinsic motivation because the ‘good deed’ can be made known to millions worldwide. The core finding is that contrary to the regular ones, social type may defy the threat of the employer (higher probability of detection, size of the sanction if detected) by engaging in more rather than less open source work, provided the number of external user is high enough. This finding suggests that the information age may facilitate the private production of a public good. The originality of this contribution lies in the prediction that certain type of workers may act against contractual incentives – a rare event in economics.